(untitled) (University of Khartoum Engineering Journal, 2022)
Gypsiferous soils are found in various countries in the world especially arid and semiarid areas, where rains fall is not sufficient to remove the gypsum section of the soil. In this study MODIS sensor data at drought day (2011/08/26) in north-west of Iraq (Al-Jazeera) was used to distinguish gypsiferous soils of the North-West Iraq. This area could be a source of dust storms. This region is characterized by the desert regions of arid and semi-dry because of scarcity of rain and vegetation cover, especially during the summer season as identified by satellite imagery in recent decades. Gypsiferous soils have been identified in Al-Jazeera region using one composite image in true colors and two composite images in false colors for MODIS sensor data. Unsupervised classification method was used to calculate the areas of these soils after that mapping gypsiferous soils in the north-west of Iraq was carried out using Arc GIS.